The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/j.1556-6676.2013.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Professional Counselors Following Hurricanes Katrina and Rita

Abstract: Professional counselors who provided services to those affected by Hurricanes Katrina and Rita completed the K6+ (screen for severe mental illness), the Posttraumatic Growth Inventory, and the Professional Quality of Life Scale. Results indicated that participants who survived the hurricanes had higher levels of posttraumatic growth than participants who served as volunteers. Both volunteer and survivor-volunteer participants were susceptible to compassion fatigue. To further resiliency, self-care strategies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 31 publications
7
50
0
Order By: Relevance
“…Ashby et al () found that strong social networks and congruent values supported resilience and, in this study, participants expressed the importance of having a community of like‐minded persons who valued social justice as they did. Lambert and Lawson () and Utsey et al () found that emotional, social, and spiritual support improved resilience, and this finding was supported in this study. Although only two respondents spoke of their current spirituality, the importance of social support was expressed by all participants.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Ashby et al () found that strong social networks and congruent values supported resilience and, in this study, participants expressed the importance of having a community of like‐minded persons who valued social justice as they did. Lambert and Lawson () and Utsey et al () found that emotional, social, and spiritual support improved resilience, and this finding was supported in this study. Although only two respondents spoke of their current spirituality, the importance of social support was expressed by all participants.…”
Section: Discussionsupporting
confidence: 87%
“…Researchers have studied resilience in terms of specific diagnostic populations as well as in various developmental populations (i.e., Utsey, Bolden, Lanier, & Williams, ). Researchers have also examined the concept of professional resilience in various professions with high burn‐out rates, such as nursing (Hodges et al, ), occupational therapy (Ashby, Ryan, Gray, & James, ), social work (Greene, Galambos, & Lee, ), and counseling (Lambert & Lawson, ).…”
Section: Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Only one study reported that it did not find a significant positive relationship between self-care and VPTG (Lambert & Lawson, 2013), and this study reported little information on how self-care was defined or assessed. Common self-care activities cited in the studies reviewed include exercise, healthy eating, engaging in hobbies, prayer, and spiritual and religious activities (Arnold et al, 2005;Barrington & ShakespeareFinch, 2013;Satkunanayagam et al, 2010;Splevins et al, 2010;Tehrani, 2010).…”
Section: Behavioural Variablesmentioning
confidence: 85%
“…Among these, emotion‐focused coping strategies may be particularly critical (Linley, Felus, Gillett, & Joseph, ). To date, however, researchers have yet to examine PTSD and emotion‐focused coping among DMHCs—a group that may be uniquely exposed to shared trauma (Bell & Robinson, ; Lambert & Lawson, ) and reliant on emotional resources to cope effectively with disaster‐related stress while supporting and assisting disaster survivors.…”
mentioning
confidence: 99%